2018
DOI: 10.1016/s2352-3018(18)30148-6
|View full text |Cite
|
Sign up to set email alerts
|

The cascade of HIV care among key populations in Indonesia: a prospective cohort study

Abstract: Australian Government Department of Foreign Affairs and Trade, WHO, and Indonesian Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 23 publications
7
101
0
2
Order By: Relevance
“…Findings of this study are suggestive of a significant relationship between PLHIV who belonged to key populations (PWIDs, TGs and sex workers) and LTFU as a treatment outcome. This finding is consistent with studies that have identified key populations as a risk factor to LTFU (21,22).…”
Section: Discussionsupporting
confidence: 92%
“…Findings of this study are suggestive of a significant relationship between PLHIV who belonged to key populations (PWIDs, TGs and sex workers) and LTFU as a treatment outcome. This finding is consistent with studies that have identified key populations as a risk factor to LTFU (21,22).…”
Section: Discussionsupporting
confidence: 92%
“…The current study had lower uptake of routine VL testing compared with those seen in Swaziland (87%), Rwanda (93.2%) and Indonesia (71.1%) 21–23. As routine VL testing was introduced recently in 2017, the early implementation challenges and barriers such as the need for repeated visits only for VL sample collection would have led to lower uptake of VL testing.…”
Section: Discussionmentioning
confidence: 62%
“…In 2015 Indonesia became a "Fast-Track" country, aiming to make rapid, efficient, innovative investments to reach HIV prevention and treatment targets, notably in Jakarta (IAPAC, n.d.). However, PLHIV retention on treatment remains low, especially among key populations (Januraga et al 2018).…”
Section: Introductionmentioning
confidence: 99%